An Open Label Prospective Study on Evaluation of Safety and Efficacy of Cilnidipine Over Amlodipine in Stage 1 Hypertensive Patients - Harlalka, S.; Roy, U.K.; Majumdar, G.; Das, K.; Mandal, P. (Kathmandu University Medical Journal, 2020)
Background Calcium channel blockers are considered the first line drug over renin-angiotensin-aldosterone system inhibitor in black population and with renin-angiotensin-aldosterone system inhibitor in non-black population with Hypertension. Amlodipine has longer biological half life and lower potential to stimulate SNS. But, is associated with reflex tachycardia and pedal oedema. Cilnidipine has potent inhibitory both on voltage gated L-type and N-type calcium channels with better anti-proteinuric effect and good tolerability. Hence, our study compared the efficacy, safety and compliance of cilnidipine over amlodipine in Stage 1 hypertensive subjects. Objective To find out antihypertensive and renoprotective effect of cilnidipine. Method The study was open-label, single centre, prospective, parallel design, randomized controlled was done in Outdoor Patient Department (OPD) of Medicine and Department of Pharmacology in Burdwan Medical College and Hospital (BMCH). Patients with stage 1 HTN received cilnidipine while the other group received amlodipine. There were 4 follow-up visits for each participant consisting of baseline, 1 week, 6 weeks and after 12 weeks. Clinical parameters including pulse rate, blood pressure and ankle oedema noted also laboratory investigations were done. Safety parameters with adverse events and compliance by traditional pill count method. Result Blood pressure was effectively decreased by both amlodipine and cilnidipine. Cilnidipine significantly decreased Pulse Rate while amlodipine increased it and the difference in Pulse Rate comparing both the groups was statistically significant. None of the ADRs were statistically significant except pedal oedema. Pedal oedema was noted only in amlodipine arm and was statistically significant. Compliance to both the drugs was excellent. Total cost of therapy was higher with cilnidipine. Conclusion Though amlodipine is preferred drug, cilnidipine should be a better alternative when we consider subjects with sympathetic over activity, proteinuria or pedal oedema.